A MASH zone revealed: The mafic complex of the Sierra Valle Fértil - Walker, Barry A. (2015)
The Sierra Valle Fértil Complex of west-central Argentina represents a section of the Ordovician (~470 Ma) Famatinian arc and exposes a continuous, tilted crustal arc section ranging in depth from ~12 to 32 km (~4-8 kbar pressure). This arc section exposes the complete compositional architecture from ultramafic and mafic rocks to upper crustal granodiorites. Field and compositional data are presented to document the deep (~6-8 kbar) mafic complex of the Sierra Valle Fértil. The mafic complex is composed of many tens to hundreds of plutonic cumulate bodies in a complex and non-regular arrangement. There is no simple compositional, kinematic or age relationship between neighboring plutons throughout the section, as expressed by cumulate compositions, emplacement horizon, size, composition, texture or style of contact. Amphibole gabbronorites and mafic tonalites dominate, but norites, amphibole websterites, troctolites and minor anorthosites are present. Amphibole is common but always as a replacement phase, and is never observed undergoing subsequent dehydration melting. Hence there is no evidence that voluminous tonalites were produced by dehydration melting of mafic precursors. A field-based, cumulate-removal fractionation model is presented that produces the observed compositional variations in five steps. Isotopic compositions of Sr and Nd deviate significantly from primitive mantle values, indicating a crustal contribution; however, this hybridization appears to have played a minor role in the major element evolution of the mafic complex. We interpret this isotopic and elemental decoupling as a byproduct of prolonged, punctuated MASH (melting, assimilation, storage, homogenization) processes in the lower crust. Isotopes may be the only residual evidence of assimilation within the mafic zone. This requires that melt removal from the cumulates was extraordinarily efficient.